THE EFFECT OF COMPENSATION MANAGEMENT TRANSPARENCY AND FINANCIAL SATISFACTION ON EMPLOYEE PERFORMANCE IN THE ERA OF INCREASING COST OF LIVING - Valensia, Clarisa Putri; Nurmalasari, Ni Made Ratih (Sekolah tinggi ilmu ekonomi pemuda, 2025)
This study aims to analyze the effect of compensation management transparency and financial satisfaction on employee performance in the era of rising living costs. The research was conducted at CV Cipta Putra Service, which employs 61 respondents selected using a saturated sampling method. The study adopts a quantitative approach with data collected through questionnaires and analyzed using SPSS version 27 through multiple linear regression analysis. The results indicate that compensation management transparency has a positive and significant effect on employee performance. This finding implies that the more transparent the company is in managing salary, bonuses, and allowances, the higher the employees’ motivation and performance levels. In contrast, financial satisfaction shows a significant but negative effect on employee performance, suggesting that focusing solely on financial rewards may reduce long-term motivation if not balanced with non-financial factors such as career development and recognition. Furthermore, both variables simultaneously have a significant influence on employee performance. These findings highlight the importance of transparent compensation policies and balanced financial and non-financial rewards in maintaining employee performance amid economic challenges. The study is expected to contribute to the development of human resource management, particularly in the field of compensation management and employee performance improvement during periods of economic instability. Keywords: Compensation Management Transparency, Financial Satisfaction, Employee Performance, Cost of Living, Human Resource Management